Simplified Automatic Atmospheric Correction for THEMIS Infrared Data. Issue 9 (14th September 2022) - Ye, Cheng; Pan, Cong; Edwards, Christopher S.; Rogers, A. Deanne
Abstract: Thermal infrared spectral data from the Thermal Emission Imaging System (THEMIS) on Mars Odyssey can provide diagnostic information to characterize Martian surface compositions. Accurately isolating the atmospheric contribution from the thermal radiance of THEMIS data is essential for surface mineralogy analysis. In this work, we present improved semi‐automatic and fully automated tools to simplify the traditional atmospheric correction method for THEMIS data. Both methods use the Thermal Emission Spectrometer surface emissivity data but in different ways. These two methods are applied to several locations that have been well documented in previous studies, to assess their capability of determining surface spectral features. The fully automatic method demonstrates its simplicity, viability, and robustness by which more consistent results have been generated for the same area across multiple THEMIS images and for areas with large topographic gradients. The tools developed in this work will broaden the utilization of THEMIS infrared spectral data to the wider planetary science community. Plain Language Summary: The Thermal Emission Imaging System (THEMIS) on the Mars Odyssey spacecraft has acquired 10 s of thousands of high spatial resolution (∼100 m/pixel), multispectral (10 bands) thermal infrared images that can be used to investigate minerals on the Martian surface at near‐global scale. In order to extract the spectral features of the surface mineralogy, the atmospheric component has to be well calculated and removed. We have developed a semi‐automatic tool and a fully automated technique to simplify the traditional atmospheric correction method for THEMIS data. These methods are applied to several locations that have been well studied by previous works, to assess their capability. The results show great potential of the fully automatic atmospheric correction method. The tools developed in this work will benefit the planetary science community to better exploit the THEMIS data sets. Key Points: We have simplified the traditional correction method and developed an automatic method to correct atmospheric effects for Thermal Emission Imaging System (THEMIS) data The automatic correction method provides a robust capability to better characterize surface spectral features from THEMIS data The automatic tools developed in this work will broaden the utilization of THEMIS infrared data to wider planetary science community